Defining the links between paternal diet, metabolic health, and reproductive fitness in mice - Eid, Nader (2024)
Dietary intake is a crucial lifestyle factor that plays a significant role in influencing an individual’s health and wellbeing. It is well established that maternal reproductive fitness and subsequent embryo development and offspring health are modified by the mother’s diet and physiology. There is strong evidence in the literature linking maternal suboptimal diet and disrupted reproductive function and offspring development. However, the role of the father and his dietary habits remained relatively less understood, and only came into the focus of animal model and human studies in recent decades. In recent years, there has been growing evidence that poor paternal diet adversely impacts sperm quality, consequently impacting on embryonic development and offspring health. In order to better understand the impact of suboptimal diet on the male testicular environment as well as metabolic and physiological health, we fed C57BL/6 male mice either a control normal protein diet (18 % casein; CD), isocaloric low protein diet (9 % casein; LPD), a low protein diet supplemented with methyl donors (betaine, choline chloride, folic acid, methionine, Vitamin B12; MDL), a high fat, high sugar Western diet (21.4 % anhydrous milk fat, 50 % carbohydrate; WD), or a Western diet supplemented with methyl donors (MDWD) for a period of at least 8 weeks. The addition of methyl donors served to test the hypothesis that their supplementation to a sub-optimal diet could potentially have ameliorative effects on gene expression and epigenetic profiles. The males were then mated with females fed a standard chow diet. Females at day 17 of pregnancy and males were culled at the end of the study period. Testes were collected from the males and processed for either morphological assessment (histology) or global gene expression profile (microarray) analysis. Liver tissue and serum were collected for metabolic assays, and DNA from stool samples was isolated and 16S sequenced for microbiome analysis. While MDL males were significantly lighter than CD upon culling, no other significant differences were observed in total body weight. However, both high fat diet groups WD and MDWD exhibited significantly greater gonadal adiposity coupled with increased liver cholesterol and a relative decrease in carcass weight. While there were no significant differences observed in mean total testicular tubule area, total perimeter, lumen area, or epithelial area between the five groups, abnormalities such as seminiferous tubule epithelial loss, tubule vacuolisation and cell separation from the basement membrane were observed significantly more frequently in testes exposed to WD and MDWD compared to the other groups. Analysis of seminiferous tubule cell populations via immunohistochemical staining revealed no change in Sertoli and germ cell numbers between the groups. However, both LPD and WD displayed a decrease in spermatogonial stem cell numbers. Array analysis of global testicular RNA revealed the upregulation and downregulation of genes involved in embryonic lethality in LPD and MDL, respectively. In both high fat groups, genes involved in abnormal cell and mitochondrial function in addition to regulatory genes of cell survival and differentiation were downregulated. While no significant differences were observed in phylogenetic diversity or species evenness between the groups when examining the gut microbiome through bacterial DNA sequencing, MDWD exhibited an increased percentage distribution of the phylum Proteobacteria compared to the other groups. While paternal diet did not seem to have an impact on maternal gestational weight, it was revealed that both low protein diet groups LPD and MDL resulted in lighter fetuses compared to CD and WD, with an increased fetal to placental weight ratio observed in WD. Taken together, these data provide further insight into testicular cytoarchitecture and global gene expression patterns in response to suboptimal paternal diet with and without key vitamin and mineral supplementation. Moreover, here the adverse effects of a high fat diet are observed without inducing obesity, suggesting an increase in adiposity at the expense of muscle mass potentially through perturbed lipid metabolism mechanisms characterised by changes in liver cholesterol and free fatty acids. Further, supplementation of either low protein or high fat diets with key methyl donors leads to different physiological and metabolic outcomes, which suggests that outcomes resultant from this form of supplementation are unique to the state of nutrition to which they are supplemented.